Sprachbewusstheit bei neu zugewanderten und in Deutschland aufgewachsenen Schüler:innen – Methodische Überlegungen und erste Ergebnisse zum Instrument MetaLing - Barberio, Teresa; Bredthauer, Stefanie; von Dewitz, Nora; Goltsev, Evghenia (Linguistik Online, 2025)
The relationship between language awareness and academic success among students has recently garnered increased attention. Previous studies on language awareness have primarily focused on bilingual students (cf. Riehl 2021; Torregrossa/Eisenbeiß/Bongartz 2022). However, the extent to which newly immigrated students in regular classes in Germany benefit from their language awareness has not yet been explored. Our project addresses this gap by examining the language awareness of newly immigrated and multilingual secondary school students using an assessment tool, MetaLing, developed within the project. This paper presents the first results of an exploratory study with 160 students, including 47 newly immigrated ones, to investing a) the level of language awareness among newly immigrated and native-born secondary school students in Germany, and b) the methodological challenges in assessing language awareness, particularly in this target group. Initial results indicate that MetaLing effectively captures language awareness without bias toward specific languages. Challenges such as technical issues and varying familiarity with online tools were noted. Future research will refine the tool and expand its application across different educational contexts.